Geographies of South Asia: empirical research and the pandemic - Butsch, Carsten; Follmann, Alexander; Keck, Markus; Müller-Blondeau, Judith Christine (Asien, 2020)
Empirical research is essential for Geography as a discipline. However, due to the current pandemic, collecting data and conducting fieldwork abroad has become an impossibility. Under current circumstances projects can only be carried out with reduced scope or have been completely put on hold, while researchers and PhD candidates are struggling with a very difficult situation - not only data-wise. Against this backdrop, we would like to use the scope of this editorial to reflect upon the meaning of the current COVID-19 pandemic both for geographical research in South Asia and for Geography as discipline. First, we will provide an overview of empirical studies that members of the South Asia Study Group have recently conducted and published. Afterward, we will briefly illustrate how the pandemic has unfolded in South Asian countries and affected their societies. Finally, we will discuss how geographers are dealing with the current situation and what we can learn from it for the future of Geography as a discipline with regional competences.